In the triangle above, the measure of A is 66°, and the measure of B is 68°. What is the measure of C?
1 answer:
Answer:
46°
Step-by-step explanation:
Given that :
Angle, A = 66°
Angle B = 68°
The sum of angles in a triangle is given by :
A + B + C = 180° (sum if angles una triangle)
66° + 68° + C = 180°
134° + C = 180°
C = 180° - 134°
C = 46°
Hence, angle C is 46°
You might be interested in
Use the chain rule:
![\frac{\mathrm dy}{\mathrm dx}=3(-3x^5+1)^2\frac{\mathrm d[-3x^5+1]}{\mathrm dx}=3(-3x^5+1)^2(-15x^4)=\boxed{-45x^4(1-3x^5)^2}](https://tex.z-dn.net/?f=%5Cfrac%7B%5Cmathrm%20dy%7D%7B%5Cmathrm%20dx%7D%3D3%28-3x%5E5%2B1%29%5E2%5Cfrac%7B%5Cmathrm%20d%5B-3x%5E5%2B1%5D%7D%7B%5Cmathrm%20dx%7D%3D3%28-3x%5E5%2B1%29%5E2%28-15x%5E4%29%3D%5Cboxed%7B-45x%5E4%281-3x%5E5%29%5E2%7D)
Answer:
85.11
Step-by-step explanation:
Answer:
Idk?
Step-by-step explanation:
An equation that fit this is c=7s
Answer:
No
Step-by-step explanation:
No, because x + x^2 cannot be grouped together.